Use of "green" hydrogen for the production of synthetic renewable methane in Ukraine - Suprun, T. (Energy and Automation, 2025)
One of the directions of development of renewable energy sources is obtaining synthetic renewable methane as a substitute for scarce natural gas, which is relevant for our country.The object of this study is renewable "green" hydrogen, which is an integral component for the production of synthetic renewable methane.The purpose of the work is to review the world experience in developing technologies for the production of "green" hydrogen to obtain synthetic renewable methane and to identify promising ways of implementing these technologies in Ukraine.The article provides a current review of technologies for the production of "green" hydrogen by means of water electrolysis using renewable energy sources (solar, wind).The research methods include the study and analysis of literary and other data, in particular, a comparative analysis of various technologies for the production of "green" hydrogen, their advantages and disadvantages, an analysis of the influence of individual parameters on these technologies, as well as their economic characteristics and application possibilities for the production of synthetic renewable methane.Despite the fact that "green" hydrogen has numerous advantages, most methods of its production are not efficient and are expensive. This is due to the relatively high price of electricity from renewable sources for its production, as well as the limitation of the number of hours of full load operation of electrolysis plants per year.In Ukraine, work on the implementation of projects for the production of "green" hydrogen has begun. The paper provides forecast estimates of the cost of hydrogen production at these plants. As shown by preliminary economic calculations of the production of "green" hydrogen and synthetic renewable methane, such production is currently not economically feasible for Ukraine. However, an analysis of the forecast of world prices for "green" hydrogen allows us to conclude that their steady trend of decline is expected. This will lead to the fact that the industrial production of synthetic renewable methane may become profitable for implementation in Ukraine in the coming decades.Key words: "green" hydrogen, synthetic renewable methane, renewable energy sources